2015
DOI: 10.1097/md.0000000000001912
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of High-Density Lipoprotein Subfractions and Hypertensive Status

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…31 Lower levels of less dense HDL particles were associated with hypertension in a large cohort of adults without diabetes, as well as the severity of coronary artery disease in patients presenting with angina. 54,55 Thus, the profile of increased cholesterol distribution in VLDL and LDL, and decreased distribution in more buoyant HDL, is associated with markers and outcomes of CVD, and is consistent with our CVD findings in youth with PCOS.…”
Section: Discussionsupporting
confidence: 89%
“…31 Lower levels of less dense HDL particles were associated with hypertension in a large cohort of adults without diabetes, as well as the severity of coronary artery disease in patients presenting with angina. 54,55 Thus, the profile of increased cholesterol distribution in VLDL and LDL, and decreased distribution in more buoyant HDL, is associated with markers and outcomes of CVD, and is consistent with our CVD findings in youth with PCOS.…”
Section: Discussionsupporting
confidence: 89%
“…reported that large HDL-C levels were inversely associated with the risk of acute myocardial infarction and may thus be protective factors 28 . Besides that, our recent studies have revealed that large HDL subfraction was negatively associated with several cardiovascular risk factors, such as serum uric acid 29 and hypertension 30 . In the current study, we found that only large HDL subfraction was negatively associated with very early CAD susceptibility, which may provide additive information regarding the different role of specific subfraction on the very early CAD incidence.…”
Section: Discussionmentioning
confidence: 97%
“…Higher values of small LDL particles and lower values of large HDL particles, as well as a reduction in LDL size, were reported in incident diabetes [10]. Decreased large HDL particles and increased small HDL particles were found in patients with hypertension [23]. However, as previously mentioned, it is still a matter of debate which subfraction of HDL is more atheroprotective [6], with reports referring a positive association between HDL3 and protection from CAD [24], in opposition to the above-referred reports in the opposite direction.…”
Section: Discussionmentioning
confidence: 99%